Le cimetière des fascistes. Comment ne pas dire l’histoire des soldats italiens décédés en captivité en Belgique et en France durant la Grande Guerre - Pierre Lannoy (Laboratoire Italien)
During the First World War, around 25,000 Italian soldiers taken prisoner during the Battle of Caporetto were sent to the rear of the Western Front in the Belgian and French territories that the Germans had occupied since 1914, condemned to work for their enemy. More than two thousand of them died there, their graves spread over more than one hundred and fifty different localities. Even before the end of the Great War, various tributes were paid to these soldiers who had died in captivity. But after 1922, the Fascist regime undertook erasing the history of Italian captivity. Thus, during the “ventennio fascista”, Belgian and French cemeteries containing Italian graves became political stages where the Fascist (re)vision of Italian military history was ardently transmitted. The aim of this article is to identify the transformation of Italian ceremonial practices in Belgium and France between 1918 and 1940. To understand the particularities of this political work, we will first describe the discourses to which the prisoners of Caporetto were subjected until the advent of fascism. By way of comparison, we will then identify the ceremonial inventions of Fascist officials in Belgian and French cemeteries, and present three ways in which they elided Italian captivity during the inter-war period. The conclusion will evoke some consequences of this memorial policy through the second half the 20th century.